Hydrodynamic chromatography using flow of a highly concentrated dextran solution through a coiled tube. (1st August 2016) - Miyagawa, Yoichi; Morisada, Shintaro; Ohto, Keisuke; Hidetaka, Kawakita
Highlights: Rheological properties of dextran solution were determined as a psedoplastic fluid. Colloidal particles of 1 and 20 μm were separated using hydrodynamic chromatography in flowing dextran solution. Starch granules were separated using hydrodynamic chromatography based on their sizes. Abstract: Separation of colloidal particles in non-Newtonian fluid is important in food engineering. Using hydrodynamic chromatography, colloidal particles and starch granules originating from corn were individually injected into dextran solutions (Mw 2, 000, 000 g/mol) flowing through a coiled tube for efficient size separation. Rheological properties of dextran solutions ranging from 50 to 250 g/L were determined, revealing pseudoplastic fluid behavior. Velocity profiles for dextran solution flow in coiled tubes were obtained from rheological power law parameters. Suspensions of colloidal particles of diameters 1.0 and 20 μm were individually injected into the dextran flows, demonstrating that dextran solutions at high concentration separated colloidal particles. Starch granules were separated by size using a dextran solution flow (250 g/L). Thus, we expect to obtain efficient separation of colloidal particles in foods using highly concentrated dextran solutions.